REALISASI MANAJEMEN POAC KURIKULUM PONDOK PESANTREN MODERN AL-MUROZZA DEPOK DALAM MEMBENTUK SANTRI BERJIWA RELIGIUS - Fatia Ainur Rosyida Fatia; Khusnul Hanifah; Marno (LP2M IAIN Sultan Amai Gorontalo, 2024)
Nowadays there are still many people who consider Islamic boarding schools to be unorganized education. In fact, curriculum management to this day is still classified as implementing an